A general definition of integrated strong motion duration and its effect on seismic demands of concrete gravity dams. (15th October 2016) - Wang, Gaohui; Wang, Yongxiang; Lu, Wenbo; Yan, Peng; Zhou, Wei; Chen, Ming
Highlights: A general integrated duration definition is proposed. Five integrated durations are considered based on the general duration definition. Correlation between integrated durations and damage measures is discussed. The vertical excitation do not always increase the seismic demands of dams. Integrated duration is positively correlated to the peak displacement measure. Abstract: Various duration definitions have been proposed to describe the effective strong motion duration based on a single component of ground motions. However, multi-component accelerograms are usually selected as the seismic excitations to evaluate the seismic performance of important infrastructures. Duration definitions able to consider the duration contributions from all components of ground motions are still lacking. In this paper, a general integrated duration definition for multi-component seismic excitations is proposed based on the existing concept of strong motion duration. According to the proposed definition, integrated bracketed duration, integrated uniform duration, and integrated significant duration are presented to measure durations for multi-component ground motions. Twenty as-recorded accelerograms with a broad range of durations are considered to investigate the correlation between integrated and single component durations. A series of nonlinear dynamic analyses are performed to quantify the influence of different integrated ground motion durations on several seismic demands (i.e. peak displacement, damage dissipation energy, and local damage index) of concrete gravity dam-reservoir-foundation systems. In addition, the results also reveal the effects of vertical seismic excitations on the seismic response of concrete gravity dams and emphasize the necessity to consider vertical motions in seismic performance assessment of such infrastructures.